Is 70Zn(d,x)67Cu the Best Way to Produce 67Cu for Medical Applications? - Nigron, Etienne; Guertin, Arnaud; Haddad, Ferid; Sounalet, Thomas (Frontiers in Medicine, 2021)
The pair of copper radionuclides 64Cu/67Cu (T1/2 = 12. 7 h/61.8 h) allows, respectively, PET imaging and targeted beta therapy. An analysis of the different production routes of 67Cu with charged particles was performed and the reaction 70Zn(d,x) route was identified as a promising one. It may allow the production of 67Cu without 64Cu. The production cross section has been measured up to 28.7 MeV. Measurements were done using the well-known stacked-foils technique using 97.5% enriched 70Zn homemade electroplated targets. These measurements complement at higher incident energies the only set of data available in nuclear databases. The results show that using a 26 MeV deuteron beam and a highly enriched 70Zn target, it is possible to produce high purity 67Cu comparable to that obtained using photoproduction. This production route can be of interest for future linear accelerators under development where mA deuteron beams can be available if adequate targetry is developed.